Effect of intravesical mitomycin-C in the treatment of superficial bladder cancer after complete transurethral resection of tumour mass - Mia, ZI; Rahman, MM; Chowdhury, MSA; Rahman, MM; Amin, ATMN; Barua, U; Karmakar, U; Kibria, SGMG (Journal of Dhaka Medical College, 2013)
DOI: http://dx.doi.org/10.3329/jdmc.v21i1.13245 J. Dhaka Med. Coll. 2012; 21(1): 88-96